Restriction fragment length polymorphism and virulence of Czech Toxoplasma gondii strains - Literák, I; Rychlík, I; Svobodová, V; Pospísil, Z (International journal for parasitology, 1998)
Restriction fragment length polymorphism analysis of chromosomal DNA from 22 strains of Toxoplasma gondii were characterised using SalI and PstI restriction endonucleases and the TGR1E specific repetitive sequence as a probe. Two virulent strains, RH and P-CZ, had previously been isolated from humans, the remaining 20 strains were isolated from animals in the Czech Republic in 1994 and 1995. Among the 20 recently isolated strains, 19 belonged to an avirulent lineage and only one strain from the wild cat Felis silvestris belonged to a virulent lineage.
Keywords: Virulence; Animals; Rabbits; Chlorocebus aethiops; Birds; polymorfismus délky restrikčních fragmentů; Rodentia; Carnivora; Genetic Markers; fluorescenční protilátková technika nepřímá; Vero Cells; shluková analýza; lidé; Mice; Vero buňky; kočky; Toxoplasma; Dogs; myši; ptáci; virulence; Cats; Humans; Polymorphism, Restriction Fragment Length; DNA, Protozoan; Czech Republic; protozoální DNA; Specific Pathogen-Free Organisms; Cercopithecus aethiops; Česká republika; králíci; hlodavci; Fluorescent Antibody Technique, Indirect; zvířata; genetické markery; Cluster Analysis; psi; organismy bez specifických patogenů